Brown Recluse Spider Bite Mediated Hemolysis: Clinical Features, a Possible Role for Complement Inhibitor Therapy, and Reduced RBC Surface Glycophorin A as a Potential Biomarker of Venom Exposure - Gehrie, Eric A.; Nian, Hui; Young, Pampee P. (PloS one, 2013)
The venom of Loxosceles reclusa (Brown Recluse spider) can cause a severe, life-threatening hemolysis in humans for which no therapy is currently available in the USA beyond supportive measures. Because this hemolysis is uncommon, relatively little is known about its clinical manifestation, diagnosis, or management. Here, we aimed to clarify the clinical details of envenomation, to determine the efficacy of the complement inhibitor eculizumab to prevent the hemolysis in vitro, and to investigate markers of exposure to Brown Recluse venom. We performed a 10-year chart review of cases of Brown Recluse spider bite-mediated hemolysis at our institution. We also designed an in vitro assay to test the efficacy of eculizumab to inhibit hemolysis of venom exposed red blood cells. Finally, we compared levels of CD55, CD59 and glycophorin A on venom exposed versus venom-naïve cells. Most victims of severe Brown Recluse spider mediated hemolysis at our institution are children and follow an unpredictable clinical course. Brown Recluse spider bite mediated hemolysis is reduced by 79.2% (SD=18.8%) by eculizumab in vitro. Erythrocyte glycophorin A, but not CD55 or CD59, is reduced after red blood cells are incubated with venom in vitro. Taken together, our laboratory data and clinical observations indicate that L. reclusa venom exposure results in non-specific antibody and complement fixation on red blood cells, resulting in complement mediated hemolysis that is curtailed by the complement inhibitor eculizumab in vitro. Glycophorin A measurement by flow cytometry may help to identify victims of L. reclusa envenomation.